Comparison of static and dynamic balance measurements among chronic and episodic migraine patients - Dumanlidağ, Seyhan; Milanlioğlu, Aysel (Arquivos de Neuro-Psiquiatria, 2021)
Background: Migraine is one of the most frequent and incapacitating headaches, with a high degree of impairment of balance control and postural stability. Objective: To investigate the effects of episodic and chronic migraine on postural balance through using static and dynamic balance tests. Methods: The study included 32 chronic and 36 episodic migraine patients and a control group of 36 healthy volunteers. Right/left single-leg static and dynamic balance tests were performed in each group with eyes open and closed using a posturographic balance platform (Techno-body Prokin). Results: No significant difference was found among episodic and chronic migraine patients and control subjects with regard to eyes-open and eyes-closed area values (eyes-open area values: p=0.559, p=0.414 and p=0.906; eyes-closed area values: p=0.740, p=0.241 and p=0.093, respectively). However, the area values were significantly higher in episodic and chronic migraine patients than in the control group, which indicates that migraine patients may have lower balance performance. Perimeter values were relatively higher which supports the idea that migraine patients have lower balance performance. Additionally, the average number of laps was significantly lower among migraine patients than in the control group, which also implies that migraine patients may have lower balance performance. Conclusion: Although no significant difference was detected between chronic and episodic migraine patients and the control group and between chronic and episodic migraine patients with regard to balance performance, chronic migraine patients seemed to have relatively lower performance than episodic migraine patients. Further studies with larger numbers of patients are needed, to investigate the relationship between these parameters and balance.
Keywords: Migraine Headaches; Posture Balance; Postural Control